2022
DOI: 10.3390/biomedicines10081957
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Overactive Bladder Syndrome May Share Common Pathophysiologies

Abstract: Metabolic syndrome (MetS) is defined by a group of cardiovascular risk factors, including impaired glucose tolerance, central obesity, hypertension, and dyslipidemia. Overactive bladder (OAB) syndrome consists of symptoms such as urinary urgency, frequency, and nocturia with or without urge incontinence. The high prevalences of metabolic syndrome (MetS) and overactive bladder (OAB) worldwide affect quality of life and cause profound negative impacts on the social economy. Accumulated evidence suggests that Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 87 publications
0
17
0
Order By: Relevance
“…Voiding dysfunctions have been linked not only to diseases of the LUT, but also to systemic diseases such as diabetes [ 26 , 27 , 28 , 29 ], obesity [ 29 , 30 ], hyperlipidemia [ 31 , 32 ], and hypertension [ 33 , 34 , 35 ] or with metabolic syndrome that is defined by impaired glucose tolerance, central obesity, hypertension and dyslipidemia [ 36 , 37 , 38 ]. Metabolic syndrome and OAB may share common pathophysiology mechanisms [ 39 ] since patients with metabolic syndrome exhibit a higher incidence of OAB [ 40 ]. Impaired purinergic signaling in the bladder has been demonstrated in animal models of diabetes, dyslipidemia, obesity and hypertension [ 41 , 42 , 43 , 44 ] and, therefore, ATP and other purines might be involved in the development of voiding dysfunctions associated with systemic diseases, including the metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Voiding dysfunctions have been linked not only to diseases of the LUT, but also to systemic diseases such as diabetes [ 26 , 27 , 28 , 29 ], obesity [ 29 , 30 ], hyperlipidemia [ 31 , 32 ], and hypertension [ 33 , 34 , 35 ] or with metabolic syndrome that is defined by impaired glucose tolerance, central obesity, hypertension and dyslipidemia [ 36 , 37 , 38 ]. Metabolic syndrome and OAB may share common pathophysiology mechanisms [ 39 ] since patients with metabolic syndrome exhibit a higher incidence of OAB [ 40 ]. Impaired purinergic signaling in the bladder has been demonstrated in animal models of diabetes, dyslipidemia, obesity and hypertension [ 41 , 42 , 43 , 44 ] and, therefore, ATP and other purines might be involved in the development of voiding dysfunctions associated with systemic diseases, including the metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are consistent with these findings, as they demonstrate the elevated succinate levels, bladder fibrosis, and impaired detrusor contractility in the fructose group. Metabolic inflammation may result in bladder fibrosis, which progresses to chronic inflammation, repeated wound healing, sustained collagen deposition, and extracellular matrix remodelling, gradually increasing the stuffiness of the bladder [ 7 ]. In this study, we found that both vinpocetine and celecoxib treatments provided anti-inflammatory effects to restore the fibrogenesis and detrusor function in FFRs.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has several limitations. First, metabolic perturbations could deteriorate bladder function through several mechanisms, such as pelvis ischemia, neuropathy, insulin resistance, and excessive succinate production [ 7 ]. In the present study, we focussed on the protective actions of vinpocetine on the succinate-modulated bladder dysfunction of the deficiency in detrusor cAMP and proinflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of the metabolic syndrome's involvement in the pathogenesis of OAB has been reported 5 . The results of the preoperative questionnaires and UDS showed a trend toward poorer storage and voiding symptoms and function in the de novo OAB group, although neither was statistically significant and the body mass index (BMI), which was listed as a risk factor, may have had an effect 3 .…”
mentioning
confidence: 99%